Innovation and Product Differentiation - Prajit K. Dutta (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
Economic theory has primarily viewed an innovation as a single, discontinuous change. Historical and empirical evidence, on the other hand, shows improvements to original technologies and quality additions to early products. We focus analysis on competition in post-discovery phase, emphasizing in particular that a key dimension to this competition is the innovations that lead to product differentiation and quality improvement. In a duopoly model with a single adoption choice, we derive endogenously the level and diversity of product innovations. We demonstrate the existence of equilibria in which firms emerge at different points of the quality spectrum. In such equilibria, no monopoly rent is dissipated and later innovators make more profits. Incumbent firms may well be the early innovators, contrary to the predictions of diversity, learning and market lock-in, in determining market expectations and hence the innovation outcomes is analyzed. Finally, innovative incentives under a cartel and social planner are contrasted with the duopoly outcomes.
Keywords: 330